Penerapan Prinsip Hak Atas Lingkungan yang Baik dan Sehat Dalam Perspektif Hak Asasi Manusia - Baso Madiong (Jurnal Pemberdayaan Hukum, 2011)
The Raight recognize and respected as such rights are believed to bring people to a level that is more prosperous, happy, safe, and just. Right to a good and healthy environment is a human rights held since he was born. Every human being born into this earth will require a good healthy and comfortable environment. The concept of the rights environment is in desperate need of reason that is rational and reasonable right whic is recognize as human rights. The destruction of environment is a violation of human roghts, because every act of a person of group of person including the state apparatus, either intentionaly.....